2014
DOI: 10.1007/s11356-014-3644-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between haze and acute cardiovascular, cerebrovascular, and respiratory diseases in Beijing

Abstract: Haze is an atmospheric phenomenon in which dry particulate pollutants obscure the sky. Haze has been associated with chronic diseases, but its relationship with acute diseases is less clear. We aimed to determine the association between haze and acute cardiovascular, cerebrovascular, and respiratory diseases, in order to determine the influence of haze on human health. We compared the number of cases of acute cardiovascular, cerebrovascular, and respiratory diseases in Beijing Emergency Center between 2006 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…China is suffering from severe air pollution with 100 million tons of biomass open burned each year (Zhang et al, 2015). The quantitative estimation of pollutant emissions for all of China (Streets et al, 2003;Tian et al, 2002;Cao et al, 2005;Zhou et al, 2017) or a certain region Zhou et al, 2015;Jin et al, 2017a) is also a vital practice, which is the base for assessing the impact of OBB on regional air quality deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…China is suffering from severe air pollution with 100 million tons of biomass open burned each year (Zhang et al, 2015). The quantitative estimation of pollutant emissions for all of China (Streets et al, 2003;Tian et al, 2002;Cao et al, 2005;Zhou et al, 2017) or a certain region Zhou et al, 2015;Jin et al, 2017a) is also a vital practice, which is the base for assessing the impact of OBB on regional air quality deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…As the largest developing country in the world, China suffers from severe air pollution, especially haze in recent decades (Madaniyazi et al, 2015). Haze is traditionally an atmospheric phenomenon where dust, smoke and other dry particles obscure the clarity of the sky (Zhang et al, 2015). Haze often occurs when dust and smoke particles accumulate in relatively dry air (Youngsin and Lim, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Our results were generally consistent with previous epidemiological studies regarding haze pollution. For example, Zhang et al showed that the daily incidence of acute cardiovascular diseases was higher on the haze days than on the non-haze days, and there was a positive relationship between cases of acute cardiovascular diseases and the number of haze days [ 13 ]. The authors further estimated an 11% (95% CI: 4%, 19%) increase in daily hospital admissions for cardiovascular diseases during a haze episode in Guangzhou, China [ 14 ].…”
Section: Discussionmentioning
confidence: 99%